Physico-Chemical Attributes and Nutritional Ingredients of Fresh Chinese Rice Wines from Different Regions - Jiao1, Jingkai; Yi2, Huaxi; Zhang2, Lanwei; Xue2, Chaohui (Asian Journal of Chemistry, 2014)
Fresh rice wine is fermented for a couple of days and very popular in the world, especially in Asian countries. Fresh rice wines differ in how they made and where they come from. For better understanding the differences among these fresh rice wines, the physical and chemical attributes and nutritional ingredients of nine kinds of rice wines from different region of China were detected in this paper. Bradford protein assay and colourimetric method, etc. were performed in this paper. The results showed that solid content ranged from 2.0435 g/100 mL to 19.2735 g/100 mL, acidity was 0.29-1.05 g/100 mL, alcoholic content was 1.9-5.1 %, protein content was 43.63-85.06 mg/100 mL, total sugar content was 0.31-15.15 g/100 mL. Amino acid was almost same in these rice wines but quite different in quantity. Three kinds of monosaccharide and two kinds of disaccharides were detected. Eight kinds of rice wines contained glucose, three kinds of rice wines contained maltose, two kinds of rice wines contained sucrose, one kind of rice wine contained fructose and xylose was undetected.